Peer Education, Nutritionist Education and Combination Education on Intake Nutrition and Iron (Fe) Against Changes of Hemoglobin in a Girls Adolescent - Irine Christiany; Adin Mu’afiro; Kiaonarni Ongko Waluyo (Humanistic Network for Science and Technology (HNST), 2021)
Hemoglobin acts as an oxygen-carrying unit from the lungs to the cells. When the formation of red blood cells is disrupted, the formation of hemoglobin levels will be low, this is called anemia. One of the causes of anemia is a lack of iron deficiency in the body. Anemia can happen to anyone, one of them is young women. Studies show that the causes of anemia in adolescents are due to irregular eating patterns, abstinence from eating protein foods, not eating vegetables, eating fast food and junk food so that the body lacks iron. Nutrition education or counseling is an educational approach to produce individual behavior in food improvement. This study compare which education among the three is more effective in improving food pattern behavior so that Hb levels will also increase. This study used pretest-posttest control group design. The research instruments were questionnaire of knowledge, FGD and easytouch GCHB. Data were analyzed using T-test. The results of this study were: 1) peer education did not have a significant effect on Hb levels, 2) education by nutritionist has a positive and significant effect on Hb (MDNutrisionist) = 0.8233, p